Identification of Lampung local potential as source of Biology learning in senior high school - Eka Wulandari; Djukri Djukri (Biosfer: Jurnal Pendidikan Biologi, 2021)
This research is a preliminary study on a small and limited scale that aims to identify local potentials in the Lampung area as a source of learning biology with conformity to the Basic Competencies in the 2013 Curriculum. This study used a qualitative method with a survey technique through an exploratory descriptive approach. Participants in this study were all biology teachers from 17 public high schools in Bandar Lampung totaling 30 teachers (5 males and 25 females). The selection of participation was done through purposive sampling technique using certain criteria. The results of the study show 18 local potentials of Lampung consisting of 6 natural resource potentials, 4 conservation areas, 4 culinary delights, 2 arts, 1 handicraft and 1 traditional ceremony. The grouping of local potentials can be related to the subject of biology at the high school level. Local potential can be categorized as use in the field of education, namely natural resources and conservation areas. It can alsobe used as practicum activities with the help of LKPD media. Furthermore,local culinary potential can be used as practicum activities on learning devices (RPP), local potentials for arts, crafts. moreover, traditional ceremonies can be used as an additional reference for enrichment programs on learning devices (RPP).